Genomic Feature of a Rare Case of Mix Small-Cell and Large-Cell Neuroendocrine Lung Carcinoma: A Case Report - Zhu, Youcai; Zhang, Feng; Yu, Dong; Wang, Fang; Yin, Manxiang; Chen, Liangye; Xiao, Chun; Huang, Yueyan; Ding, Feng (Frontiers in Oncology, 2022)
Background: Cases with both of small cell lung cancer (SCLC) and large cell neuroendocrine lung carcinoma (LCNEC) were rarely reported. Although typical cases are morphologically distinct, the distinction between LCNEC and SCLC is still controversial, with some LCNECs showing close morphologies with SCLC. Here we reported on a patient who had tumor with a mix of SCLC and LCNEC, and uncovering these components’ histological and genomic features. Case presentation: A 59-year-old man was diagnosed with lung cancer and had resection surgery in our hospital. The H&E and immunohistochemistry staining revealed that the tumor had 30~35% LCNEC and 65~70% SCLC cells. The whole-exome sequencing (WES) identified no potentially actionable alteration in the tumor sample, but found five alterations all with allele frequency over 90%, including TP53 p.R273H, MYH8 p.Q1814K, SLC17A6 p.W505L, PTPN5 p.M40I and RB1 p.L267X. The genomic results supported that these two different components shared a similar dominant clonal origin. Furthermore, fluorescence in situ hybridization analysis revealed that the LCNEC have a higher copy number of MET than the SCLC component, while without notable difference in the copy number of HER2 and TP53. Chemotherapy with pemetrexed and carboplatin was administrated for two cycles after the surgery. Though the chest CT showed remission in lung, but he was diagnosed with bone metastasis in one year later. Then, he received chemotherapy with etoposide and carboplatin but had severe side-effect, leading to the discontinuing the regime. Unfortunately, he returned to local hospital with supportive care and deceased shortly after. Conclusion: Based on these observations, we proposed that LCNEC and SCLC components in this patient may have a common clonal origin with dual mutations in TP53 and RB1, while the chromosome instability may cause multiple independent conversion that leads to LCNEC or SCLC morphologies.